유전자원의 효율적 활용을 위한 데이터 구성: 메밀의 사례 연구 - 한경덕; 정용석 (Korean journal of breeding, 2022)
The breeding objective for crops changes constantly due to environmental changes, customer requirements, and farming convenience,among other factors. As breeding takes a long time, suitable mating candidates must be obtained from the beginning. In this study, we proposea breeder-friendly system and datasets. We investigated 11 traits that affect adaptation to the cultivation environment in Jeju Island using27 buckwheat germplasms and selected good germplasms for breeding new cultivars. Data on the various traits of the target crop could assistbreeders or researchers in identifying the traits of each genetic resource that will facilitate the development of new cultivars that suit therequirements of customers. Therefore, this study suggests establishing a breeder-friendly system and datasets in GenBank. KCI Citation Count: 0